Alternating or continuous exposure to cafeteria diet leads to similar shifts in gut microbiota compared to chow diet. Issue 1 (27th May 2016) - Kaakoush, Nadeem O.; Martire, Sarah I.; Raipuria, Mukesh; Mitchell, Hazel M.; Nielsen, Shaun; Westbrook, R. Fred; Morris, Margaret J.
Abstract : The gut bacteria of rats either continuously fed standard chow or palatable cafeteria diet are compared to a third group cycled between these diets (4/3 days each wk) over 16 wks. Body weight and metabolic parameters of cycled rats were intermediate between those of the other diet groups. Gut bacteria of cycled rats were nearly indistinguishable from rats under constant cafeteria diet, and both groups were different to the chow group. Thus, any exposure to junk food affects gut bacteria. Abstract : Scope: Overconsumption of energy‐rich food is a major contributor to the obesity epidemic. The eating habits of many people are characterized by the cycling between overconsumption of energy‐rich foods and dieting, the effects of which on the microbiota are currently unknown. Methods and results: We compared the fecal microbiota of rats either continuously fed chow or palatable cafeteria diet to a "cycled" group switched between the two diets (chow for 4, cafeteria for 3 days/wk, n = 12/group) over 16 wk. Enriched bacterial metabolic pathways were predicted, and a range of metabolic parameters was correlated to microbial taxa and pathways. Cycled rats showed large excursions in food intake on each diet switch. When switched from chow to cafeteria, they overconsumed, and when switched back to chow they underconsumed relative to those maintained on the two diets. Metabolic parameters of cycled rats were intermediate between those of the other diet groups ( p < 0.05). The microbiota of cycled rats was nearly indistinguishable from rats under constant cafeteria diet, and both groups were significantly different to the chow group. Correlation analyses identified microbial metabolic pathways associated with an obese phenotype. Conclusion: These data suggest that continuous or intermittent exposure to palatable foods have similar effects on the gut microbiota.